Thigh muscle activities in elite rowers during on-water rowing - Guevel, A.; Boyas, S.; Guihard, V.; Cornu, C.; Hug, F.; Nordez, A. (International Journal of Sports Medicine, 2011)
This study analysed the muscle activity levels and patterns of the major thigh muscle activation during training sections at different intensities of on-water rowing. 9 experienced rowers performed 2 imposed-pace sections (B1 and B2) and 2 maximal-speed sections (start, 500 m) of on-water rowing. The knee angle, power output, mean torque and stroke rate were measured using specific instrumentation and were synchronised with surface electromyography signals of 5 superficial quadriceps and hamstring muscles. B1 and B2 sections were not significantly different regarding mechanical parameters and EMG activities, while the start phase induced large differences. The EMG patterns for B1, B2 were similar (cross-correlation coefficients (CC) ranged between 0.972-0.984) and the moderate CC found between both B1 and start (0.605-0.720) and B2 and start (0.629-0.720). Our results suggest that the hamstring muscles have a motor action and contribute to the power production during the leg drive. During an all-out 500 m section, a decrease in power and stroke rate was found (up to 20%). However, EMG patterns were not time shifted for all muscles. During the leg drive, the muscle activity levels of the quadriceps muscles were unchanged, while the activity of the hamstring muscles decreased.